Penerapan Model Problem Based Learning Berbantuan e-Module Fungsi untuk Meningkatkan Kemampuan Pemecahan Masalah - Maydatul Zannah; Faisal Faisal; Fenny Anggreni (Supermat : Jurnal Pendidikan Matematika, 2025)
The low level of students’ mathematical problem-solving abilities and the frequent use of conventional approaches in the learning process are the main reasons for conducting this study. This study aims to examine the implementation of a problem-based learning model supported by an e-module to improve mathematical problem-solving abilities on the topic of functions. This study applies a quantitative approach designed in a pre-experimental design with one pretest/posttest group. The research respondents were 25 grade VIII students at one of the public schools in Langsa District in the 2024/2025 academic year who were selected purposively. The instrument used in the data collection process was an essay test derived from the Polya problem-solving framework, which had previously been assessed for validity and reliability. This study analyzed the results of descriptive test data showing that the average pretest score of 62.52 increased to 74.04 in the posttest, so there was an increase of 11.52 points after the implementation of PBL learning assisted by e-modules. The pretest and posttest data had a significance value of 0.000 > 0.05 according to the Kolmogorov–Smirnov normality test, indicating that both were normally distributed and met the requirements for the paired sample t-test. Thus, the application of learning with the Problem Based Learning (PBL) model assisted by e-modules has been proven to improve students' mathematical problem-solving abilities in the main material of functions.